1995
DOI: 10.1007/bf00222209
|View full text |Cite
|
Sign up to set email alerts
|

Application of two microsatellite sequences in wheat storage proteins as molecular markers

Abstract: In eukaryotes, tandem arrays of simple-sequence repeat sequences can find applications as highly variable and multi-allelic PCR-based genetic markers. In hexaploid bread wheat, a large-genome inbreeding species with low levels of RFLP, di- and trinucleotide tandem repeats were found in 22 published gene sequences, two of which were converted to PCR-based markers. These were shown to be genome-specific and displayed high levels of variation. These characteristics make them especially suitable for intervarietal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(97 citation statements)
references
References 15 publications
0
92
0
2
Order By: Relevance
“…We took advantage of microsatellite markers psp2999 and psp3000 present within the coding sequences of genes Glu-A3 and Gli-B1, respectively (Devos et al, 1995), to introgress different Glu-3/Gli-1 alleles into ProINTA Imperial and investigate their effects on gluten strength. We developed Near Isogenic Lines (NILs) through a program of six cycles of backcrossing to ProINTA Imperial (BC 6 ), self-pollination of heterozygous BC 6 plants and selection of homozygous BC 6 F 2 plants.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…We took advantage of microsatellite markers psp2999 and psp3000 present within the coding sequences of genes Glu-A3 and Gli-B1, respectively (Devos et al, 1995), to introgress different Glu-3/Gli-1 alleles into ProINTA Imperial and investigate their effects on gluten strength. We developed Near Isogenic Lines (NILs) through a program of six cycles of backcrossing to ProINTA Imperial (BC 6 ), self-pollination of heterozygous BC 6 plants and selection of homozygous BC 6 F 2 plants.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Different Glu-3/Gli-1 alleles were introgressed into ProINTA Imperial taking advantage of microsatellite markers psp2999 and psp3000 present within the coding sequences of genes Glu-A3 and Gli-B1, respectively (Devos et al, 1995). A previous survey of Argentine wheat varieties (Manifesto et al, 2001) identified nine different alleles for psp2999 and psp3000 in the varieties 38 MA, Retac on INTA, Buck Poncho, Buck Manantial, Klein Toledo and Norkin Churrinche, which were selected as donor parents of new Glu-A3/Gli-A1 and Glu-B3/Gli-B1 alleles in this study (Table 1).…”
Section: Development Of Isogenic Linesmentioning
confidence: 99%
“…This information would help breeders to incorporate useful genetic variation into adopted gene pools by selecting for marker alleles linked to loci controlling important agronomic or quality traits (Tanksley and McCouch 1997). Several authors have studied genetic diversity in wheat by using different molecular markers, such as microsatellite (Devos et al 1995;Bohn et al 1999;Donini et al 2000;Manifesto et al 2001;Christiansen et al 2002;Huang et al 2002;Dreisigacker et al 2004;Fufa et al 2005), amplified DNA fragment polymorphism markers (Schut et al 1997;Barrett et al 1998;Manifesto et al 2001), and random amplified polymorphic DNA markers (Joshi and Nguyen 1993). Microsatellite markers, also known as simple sequence repeats (SSR), have proved to be the most suitable molecular markers for studying genetic diversity in wheat because of its multi-allelic nature, chromosome specificity, high polymorphism, and distribution throughout the genomes (Röder et al 1998a(Röder et al , 1998b.…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellites are commonly used to study genetic relationships between genotypes within species because of their high level of polymorphism (Devos et al 1995;Plaschke et al 1995;Korzun et al 1997). In addition, microsatellites exhibit a codominant inheritance (Hernández et al 2002), which is essential for effective discrimination between closely related lines (Akkaya et al 1992).…”
mentioning
confidence: 99%